The Wnt Signaling Pathway in Diabetic Nephropathy - Wang, Haiying; Zhang, Ran; Wu, Xinjie; Chen, Yafen; Ji, Wei; Wang, Jingsuo; Zhang, Yawen; Xia, Yong; Tang, Yiqun; Yuan, Jinxiang (Frontiers in Cell and Developmental Biology, 2022)
Diabetic nephropathy (DN) is a serious kidney-related complication of both type 1 and type 2 diabetes and the second major cause of end-stage kidney disease. DN can lead to hypertension, edema, and proteinuria. In some cases, DN can even progress to kidney failure, a life-threatening condition. The precise etiology and pathogenesis of DN remain unknown, although multiple factors are believed to be involved. The main pathological manifestations of DN include mesangial expansion, thickening of the glomerular basement membrane, and podocyte injury. Eventually, these pathological manifestations will lead to glomerulosclerosis, thus affecting renal function. There is an urgent need to develop new strategies for the prevention and treatment of DN. Existing evidence shows that the Wnt signaling cascade plays a key role in regulating the development of DN. Previous studies focused on the role of the Wnt canonical signaling pathway in DN. Subsequently, increased research on the mechanism of the Wnt non-canonical signaling found that Wnt/Ca2+and Wnt/PCP also have essential roles in DN. In this review, we summarize the specific mechanisms of Wnt signaling in the occurrence and development of DN in podocyte injury, mesangial cell injury, and renal fibrosis. Also, to elucidate the significance of the Wnt canonical pathway in the process of DN, we uncovered evidence supporting that both Wnt/PCP and Wnt/Ca2+ signaling are critical for DN development.